2017
DOI: 10.1007/s00784-017-2273-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bleaching agent extracts on murine macrophages

Abstract: The addition of an antioxidant can downregulate unfavorable effects of dental bleaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In contact with human cells, -OH radical can induce lipid peroxidation and DNA alteration followed by cell lysis and death [ 5 ]. Previous in vitro study [ 10 ] showed irreversible cytotoxic effects in cells exposed to 20% CP for 1 h. However, although no genotoxicity effect of lower concentration of CP was used [ 6 , 11 13 ], a closer view of clinical studies that evaluated higher concentrated bleaching materials for at-home technique showed controversial results in terms of micronucleus frequency [ 11 , 13 – 15 ]. Genotoxicity is the ability of a substance to damage the human cells genetic content [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contact with human cells, -OH radical can induce lipid peroxidation and DNA alteration followed by cell lysis and death [ 5 ]. Previous in vitro study [ 10 ] showed irreversible cytotoxic effects in cells exposed to 20% CP for 1 h. However, although no genotoxicity effect of lower concentration of CP was used [ 6 , 11 13 ], a closer view of clinical studies that evaluated higher concentrated bleaching materials for at-home technique showed controversial results in terms of micronucleus frequency [ 11 , 13 – 15 ]. Genotoxicity is the ability of a substance to damage the human cells genetic content [ 16 ].…”
Section: Introductionmentioning
confidence: 99%